Pengaruh Kecepatan Translasi dan Temperatur Pemanas Landasan Pelat Pada Friction Stir Welding Terhadap Kekuatan Bending Sambungan Las AA1100 - Mohammad Irfan Yudhistira; Elka Faizal (International Forum of Researchers and Lecturers, 2025)
Alumunium AA1100 is widely used in flat plate products such as heat exchanger fins and lightweight structural panels, yet it’s welding process still requires optimization. This study aims to determine the effect of tool traverse speed and backing plate preheating temperature on the bending strength of AA1100 joints produced by Friction Stir Welding (FSW). Experiments were conducted at three levels of each factor with three replications per combination: traverse speeds of 10 mm/min, 20 mm/min, 30 mm/min, and preheating temperatures of 200 °C, 250 °C, 300 °C. Results showed the travers speed, preheating temperature, and their interaction all had significant effects on bending strength (P-Value < 0,05). The optimal combination 30 mm/min traverse speed and 200 °C preheating yielded a bending strength of 238,95 Mpa. The regression model’s coefficient of determination was 97,16%, indicating an exellent fit. Thus, selecting the right FSW parameters can significanly enhancejoint quality.